2016
DOI: 10.2214/ajr.15.14948
|View full text |Cite
|
Sign up to set email alerts
|

Wrist Traction During MR Arthrography Improves Detection of Triangular Fibrocartilage Complex and Intrinsic Ligament Tears and Visibility of Articular Cartilage

Abstract: Wrist MR arthrography with axial traction significantly improved the visibility of articular cartilage and the detection and visibility of tears of the TFCC and intrinsic ligaments. The results favor more widespread use of traction during MR arthrography of the wrist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
1
21
0
3
Order By: Relevance
“…Our previous study, which used an identical traction system as the one in this study for the wrist, showed that this degree of upper limb traction is well tolerated by patients. 23 We used these weights (5 kg for females and 7 kg for males) for elbow traction as no previous study has investigated elbow traction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study, which used an identical traction system as the one in this study for the wrist, showed that this degree of upper limb traction is well tolerated by patients. 23 We used these weights (5 kg for females and 7 kg for males) for elbow traction as no previous study has investigated elbow traction.…”
Section: Discussionmentioning
confidence: 99%
“…MRA with axial traction has been evaluated with success in the shoulder, [11][12][13] hip, [14][15][16][17][18][19][20][21] knee, 22 wrist, [23][24][25][26][27][28][29][30] ankle 31,32 and metatarsophalangeal 33 and metacarpophalangeal joints. 34 To the best of our knowledge, there is no study comparing MRA of the elbow with and without traction.…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde ultrasonografinin el bileği enjeksiyonunda etkinliğini gösteren çalışmalar mevcuttur (6)(7)(8)(9)(10)(11). Radyolojik olarak kontrastın eklem içine ve intrensek ligaman rüptürlerine bağlı komşu kompartımanlara geçişini en iyi gösteren yöntem MR artrografidir (3,(4)(5)(6)(7)(8)(9)(10)(11)(12)…”
Section: Methodsunclassified
“…The accuracy of TFCC tear has increased from 83% to 98% (48) (Figure 20). MR with traction is well tolerated and does not increase the examination time too much as almost all the preparation work is completed before entering the scanning room (48).…”
Section: Mr Wrist With Tractionmentioning
confidence: 99%